Pengaruh Model Pembelajaran Berbasis Masalah dengan Pendekatan Saintifik terhadap Keterampilan Berpikir Kritis Siswa - Mirawati, Baiq; Meilani, Rini; Hunaepi, Hunaepi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2017)
This study aims to determine the effect of the problem-based learning model (PBL) with a scientific approach to critical thinking skills of class X students of Al-Ma’arif Pandan Indah Islamic High School 2016/2017 academic year. The type of research used is quasi-experiment with Nonequivalent control group design. The population in this study were all students of class X Islamic High School Al-Ma’arif Pandan. The sample used consisted of two classes taken using nonprobability sampling techniques, namely class XA as the experimental class, and class XB as the control class. The technique of collecting data on the implementation of RPP using the observation sheet and critical thinking skills of students was measured using a test in the form of a description question that had been validated by 2 expert experts. Data analysis of critical thinking skills carried out by t-test found that t-count = 2.58> 2.042. Based on the results of the analysis it can be concluded that the problem-based learning model with a scientific approach significantly influences students' critical thinking skills.